Semiquantitative Analysis of Apolipoprotein A‐I Modified by Advanced Glycation End Products in Diabetes Mellitus - Kurosaki, Yoshifumi (J Clin Lab Anal, 2013)
BACKGROUND: Apolipoprotein A‐I (Apo A‐I), the major component of high‐density lipoprotein (HDL), is modified by reactive α‐oxoaldehydes, such as methylglyoxal (MG) and glycolaldehyde (GA), and these modifications affect the function of Apo A‐I. GA‐ and MG‐modified Apo A‐I serum levels were semiquantitatively evaluated in diabetic patients to elucidate the association of each protein with diabetes and to determine its appropriateness as a serum marker of diabetes. METHODS: We enrolled 44 subjects in this study (diabetic subjects, n = 24; nondiabetic subjects, n = 20). GA‐ and MG‐modified Apo A‐I levels in serum were determined by sandwich enzyme‐linked immunosorbent assay (ELISA) by using anti‐GA or anti‐MG antibody and anti‐Apo A‐I antibody. RESULTS: The GA‐modified Apo A‐I levels did not significantly differ between the diabetic and nondiabetic subjects (1.00 ± 0.38 vs. 0.96 ± 0.22). However, the MG‐modified Apo A‐I levels in the diabetic subjects were significantly higher than those in the nondiabetic subjects (1.33 ± 0.52 vs. 0.90 ± 0.20). In addition, MG‐modified Apo A‐I levels correlated with the glycated hemoglobin (HbA1c) levels, HDL‐cholesterol levels, and the homeostasis model assessments of insulin resistance, which are indicators of insulin resistance. CONCLUSION: The MG‐modified Apo A‐I level may be an indicator of diabetic dyslipidemia and insulin resistance.